Real-world evidence of the efficacy and tolerability of trabectedin in patients with advanced soft-tissue sarcoma - Sande González, Luis Miguel de; Martin-Broto, Javier; Kasper, Bernd; Blay, Jean-Yves; Le Cesne, Axel (Expert review of anticancer therapy, 2020)
The efficacy and tolerability of trabectedin in patients with soft tissue sarcoma (STS) have been confirmed by various clinical studies involving lipo- and leiomyosarcomas as well as many other subtypes including translocation-related sarcomas. These data have been obtained from randomized phase II and III clinical trials. Studies in real-world clinical practice are necessary to bridge the efficacy-effectiveness gap and complete the body of evidence. Furthermore, reinforcing clinical experience with data from routine clinical practice allows drug management to be optimized and clinical benefits to be maximized. The present review provides the most significant data on the efficacy of trabectedin in real-world studies, and the interpretation of real-world experience with trabectedin, in patients with advanced STS. Trabectedin has demonstrated durable disease control and an adequate safety profile, indicating it to be a suitable long-term treatment drug associated with a good quality of life. Personalized strategies and individualized objectives are the way forward in the management of STS.
Gesehen am 02.09.2025